Hyperurikemie z perspektivy nefrologického pacienta - Bandúr, Štěpán (Vnitrni lekarstvi, 2020)
Hyperuricemia is a common laboratory finding in different types of patients. Except of those with acute or chronic gout, it is frequently found in patients with metabolic syndrome, patients with malignancies or renal impairment - acute kidney injury (AKI) and chronic kidney disease (CKD). Hyperuricemia might cause renal dysfunction or might be a part of laboratory abnormalities associated with loss of renal function as well. There is also large body of evidence of hyperuricemia as a potential cardiovascular (CV) risk factor, which might even more increase CV risk in CKD patients. Association of asymptomatic hyperuricemia and progression of CKD remaines controversial, as well as indication for hypouricemic treatment in this clinical setting.
Keywords: uric acid; hyperuricemia; Uric Acid; acute kidney injury (AKI); rizikové faktory; progrese nemoci; hyperurikemie; cardiovascular risk; Humans; lidé; kyselina močová; Renal Insufficiency, Chronic; chronická renální insuficience; Risk Factors; Disease Progression; Hyperuricemia; chronic kidney disease (CKD)